ETIKA PEMBELAJARAN DALAM KONTEKS PENDIDIKAN KEWARGANEGARAAN: SUATU ALTERNATIF MEMBANGUN PILAR PENDIDIKAN - Purwatiningsih, Ary (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
Citizenship education is an important aspect in the education system which aims to form citizens who are aware of their rights and obligations in a democratic society. In this context, learning ethics plays a very important role in forming a strong basis for achieving this goal. This article illustrates the importance of learning ethics in civic education learning as an alternative for building strong educational pillars. Learning ethics includes values, norms and principles that must be applied in the educational process. In the context of citizenship education, learning ethics involves developing awareness of human rights, democratic principles, pluralism, and active participation in political and social life. This learning ethic not only affects students, but also teachers, the curriculum, and the entire educational environment. The method used in this research is a qualitative approach, with literature study. This article also discusses several key elements in building the pillars of citizenship education through learning ethics. First, citizenship education must encourage a deep understanding of democratic values and human rights. Second, learning ethics must promote inclusive attitudes and respect for diverse cultures and political views. Third, students must be empowered to participate actively in social and political life, including in democratic decision-making processes. Through this approach, learning ethics becomes a strong foundation for building pillars of sustainable and relevant citizenship education. By strengthening ethical understanding in learning, we can help students become responsible, caring, and active citizens in building a just and democratic society.